Pathological optimist [videorecording (DVD)] - Bailey, Miranda, 1977-; Wakefield, Andrew J (Gravitas Ventures, 2018)
Examines the circumstances behind the Tribeca Film Festival scandal surrounding the film "VAXXED : from cover-up to controversy," and the doctor whose study suggested a link between the MMR vaccine and autism.